112k views
2 votes
Y = 6x + 11
2х - Зу = 7

User Frogblast
by
5.2k points

1 Answer

1 vote

9514 1404 393

Answer:

(x, y) = (-2.5, -4)

Explanation:

Since you are given an expression for y, it is convenient to substitute that into the second equation.

2x -3(6x +11) = 7

2x -18x -33 = 7

-16x = 40 . . . . . . add 33

x = -40/16 = -2.5

Using the equation for y, we find ...

y = 6(-2.5) +11 = -15 +11 = -4

The solution is (x, y) = (-2.5, -4).

Y = 6x + 11 2х - Зу = 7-example-1
User Michaelpri
by
7.1k points